SC of polar codes based normalized MS algorithm - Hasan, Alaa A.; Marsland, Ian D. (2017 8th IEEE Annual Information Technology, Electronics and Mobile Communication Conference (IEMCON), 2017)
In this paper, the principle of normalized minimum-sum (NMS) polar decoding process is explored. It is demonstrated that with one properly chosen parameters for NMS algorithm, performances approach to that of the sum-product (SP) algorithm can be achieved. As well, the complexity reduction is realized by calculating a linear function instead of nonlinear function. Simulation results for successive cancellation (SC) polar codes with code length moderately long validate the proposed approximation.